STYLISTICS ANALYSIS OF THE BEATLES’ SELECTED POPULAR SONGS - Octofiany, Utami; Halim, Abdul (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
The Beatles were an English rock band formed in 1960 in Liverpool. They were largely recognized as the greatest and most influential act of the rock period, with members John Lennon, Paul McCartney, George Harrison, and Ringo Starr. From 1965 to 1969, the Beatles released what many consider to be their best work, including the innovative and widely influential albums Rubber Soul (1965). Revolver (1966), Sgt. Pepper's Lonely-Hearts Club Band (1967), The Beatles (commonly known as the White Album, 1968), and Abbey Road (1969). This study aims to analyze the stylistic features of the popular selected songs; Hey Jude (1986), Let It Be (1970), Yesterday (1965), Here Comes the Sun (1969). The research method that the author used is library research method and the analytical method used is textual analysis. The author analyzes the figurative language on semantic level and the Phonetic devices on phonetic level of stylistic in selected popular songs to understand the difference between each type in figurative language and also phonetic devices. The conclusion of this thesis shows that there are 28 figurative languages found with 8 types: 4 Simile, 6 Metaphor, 3 Personification, 2 Metonymy, 5 Symbol, 2 Paradox. 5 Hyperbole and 1 Irony. The result for phonetic devices shows that in selected songs, there are 14 rhyme, 19 alliteration, 27 assonance, 32 consonants in total from all the selected songs.